2000
DOI: 10.1103/physrevb.61.r2472
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-atom chain formation in the core of nanotubes

Abstract: Here we report the observation of a linear carbon-atom chain, synthesized using an arc discharge from a graphite double anode. We use high-resolution TEM to evidence the formation of a carbon-atom chain along the axis of a needlelike structure consisting of concentric cylindrical graphitic shells. The atomic chain in the core of the innermost cylinder, by calculations on the basis of van der Waals interactions, demonstrates an extremely high thermal stability ͑up to 4200 K͒ and exhibits high mechanical strains. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
80
2
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 14 publications
6
80
2
2
Order By: Relevance
“…The high stabilization energies obtained in the present systematic study support the experimental observation of the linear chain hydrocarbon, stabilized by physisorption, inside the multi-walled CNTs [28,29], in spite of the fact that the isolated long linear chain of carbon clusters are considerably less stable than the cyclic form [34 -36]. Using density functional calculations with simulated annealing, Jones and coworkers reported that C 4 , C 6 and C 10 linear chains inside (5,5) SWNT are destabilized [40].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The high stabilization energies obtained in the present systematic study support the experimental observation of the linear chain hydrocarbon, stabilized by physisorption, inside the multi-walled CNTs [28,29], in spite of the fact that the isolated long linear chain of carbon clusters are considerably less stable than the cyclic form [34 -36]. Using density functional calculations with simulated annealing, Jones and coworkers reported that C 4 , C 6 and C 10 linear chains inside (5,5) SWNT are destabilized [40].…”
Section: Resultssupporting
confidence: 87%
“…Wang et al observed the unsaturated linear carbon atom chain formation in the core of an innermost nanotube and further demonstrated that the thermal and mechanical stability of the carbon atom chain inside the nanotube are mainly due to van der Waals forces [28]. Recently, Zhao et al have reported unsaturated linear carbon chain of more than 100 atoms at the innermost tube of the multi-walled CNTs (MWNT) [29].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The possibility of stabilizing sp chains in cluster-assembled nanostructured carbon films [15] and inside carbon nanotubes [16,17] Cluster-assembled films were grown in ultra high vacuum (~ 10 -9 mbar) by depositing on glass substrates a supersonic beam of carbon clusters produced by a pulsed microplasma cluster source as described in detail in refs. [19,20]; two parallel gold contacts were previously evaporated on the substrate (200 nm thick, 4 mm long and 0.8 mm separation).…”
mentioning
confidence: 99%
“…These chains exhibited remarkably good stability with a length up to few nanometres even under the irradiation of 120 keV electron beams. The possibility of stabilizing sp chains in cluster assembled nanostructured carbon films [5] and inside carbon nanotubes [6,7] has also been demonstrated suggesting that pure carbon sp 2 systems containing sp hybridization can be synthesized. Recent experiments [8] suggest that cumulenic oligomers can be stabilized in a sp 2 carbon matrix and can be used to control the electrical properties and the nanostructure of the material by controlling the density and the decay of sp metallic chains [9].…”
mentioning
confidence: 97%